Synthesis, characterization, crystal structure and DFT study of a new compound 3-(4-(2, 4-dimorpholinopyrido[2, 3-d]pyrimidin-6-yl)phenyl)-1, 1-diethylurea. Issue 1 (1st September 2022) - Liao, Wanpeng; Liu, Tong; Wu, Feng; Dai, Hongyu; Deng, Liyuan; Zhou, Zhixu; Zhao, Chunshen
Abstract: In this study, the compound 3-(4-(2, 4-dimorpholinopyrido[2, 3- d ]pyrimidin-6-yl)phenyl)-1, 1-diethylurea was prepared. The synthesis of the compound was confirmed using 1 H NMR, 13 C NMR, HRMS and FT-IR spectroscopies. The crystal structure of the title compound was optimized using by density functional theory (DFT) calculations, and the molecular structure of the crystal was compared with theoretical calculations. The results show that the molecular structure optimized by DFT is essentially identical to the crystal structure determined by X-ray single-crystal diffraction. Additionally, the optimal structure and frontier orbital energy were calculated using DFT.